Inclusive Education Strategy to Overcome Learning Barriers for Students with Special Needs at SDN Madyopuro 4 - Maulidha, Arini Putri; Permata, Santy Dinar (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2024)
The current era of government and community attention refers to the increasing population of children with special needs in Indonesia, thus encouraging the implementation of inclusive education in all educational institutions. The purpose of this research is to describe whether inclusive education strategies can overcome learning barriers in students with special needs at SDN Madyopuro 4. This research uses a descriptive qualitative approach with descriptive analysis methods and data collection techniques in the form of interviews, observation, and documentation. The results of this study indicate that the application of inclusive education strategies at SDN Madyopuro 4 in overcoming learning barriers for students with special needs, especially students with learning disabilities (slow learners) is very appropriate, such as curriculum suitability, the use of varied teaching methods and strategies to suit the needs of each student, and the active role of both class teachers and Special Assistance Teachers (GPK) can have a positive impact on students with learning disabilities. Overall, it can be concluded that the importance of collaboration of all parties in building inclusive education according to the expected goals so as to provide sustainable efforts in improving the quality of inclusive education to support effective learning for each student. Keywords: Inclusive Education, Learning Disabilities, Children with Special Needs